Heroin use among clients receiving methadone treatment in Dar es Salaam Tanzania: a qualitative study - Mosha, Idda H. (International Journal Of Community Medicine And Public Health, 2023)
Background: Simultaneous heroin use among methadone-maintained clients is a recognized phenomenon worldwide. Tanzania is the first sub-Saharan African country to offer methadone treatment. This study explored reasons for heroin use among clients on methadone treatment clinics in Dar es Salaam, Tanzania. Methods: This was exploratory cross-sectional study. Purposive sampling was used to select ten study participants. In in-depth interview guide was used to collect data. The interviews were conducted in Kiswahili and lasted for about sixty minutes. Audio-recordings of the interviews were transcribed verbatim and translated into English. Transcribed data was analysed and subjected to thematic analysis with the help of Nvivo 12 software. Results: Many reasons were mentioned for concurrent use of heroin and methadone among clients on methadone treatment. Some of the mentioned reasons were inadequate methadone dose, treatment, healthcare providers’ attitudes, and healthcare provision environment, lack of family support, peer influence homeless and easy availability of heroin. Conclusions: Different measures should be taken by methadone programs and stakeholders to overcome concurrent use of heroin and methadone among clients receiving methadone treatment.